Design Optimisation : Between Aesthetic And Functional Consideration - Naamandadin, Nurul Akmam (Universiti Sains Malaysia, 2005)
This dissertation will, in many circumstances, figure out the awareness to create excellent design as good as possible with the consideration of aesthetic values and appropriate with it function; and it is a great honour to conclude that supportive networks are also precisely the ingredients that made this work not only feasible, but greatly fulfilling. The inspiring and unique atmosphere at Universiti Sains Malaysia proved an invaluable resource, and my gratitude goes out to my lecturers whose rich experience and inspiration has provided consistent momentum to expand my boundaries of perception and intellect. I am very thankful to my supervisor Prof. Madya Dr. Omar Osman who is played in part of this as well, by reading segments of this dissertation, gave valuable feedback and ideas.